The Scottish Orthodontic Peer Review project: the outcome of treatment and standard of record keeping by orthodontic specialist practitioners in Scotland. (3rd July 2018) - Isherwood, Grant; Pencovich, Ross; Burnside, Girvan; Miller, Simon
ABSTRACT: Objectives: Assess occlusal outcomes of treatment and clinical record keeping in specialist practice in Scotland. Design: A retrospective cohort study. Setting: Specialist practices in Scotland. Participants: Specialist orthodontists in Scotland. Methods: Every specialist practitioner in Scotland (51) was invited to take part in the peer review project with 38 (76%) enrolled. Scotland was split into four geographical areas, and each practitioner matched with a colleague from the same area. Practitioners took one day to visit their colleague and score 30 consecutively treated NHS cases using the Peer Assessment Rating (PAR) index. They also assessed the quality of the records taken. Practitioners then swapped roles and assessed their partner's occlusal outcomes and records. Results: The mean pretreatment PAR score was 28.6 (SD 3.5). Mean posttreatment PAR score was 3.5 (SD 1.2). Mean reduction in PAR score was 25.1 (SD 3.8). Mean percentage PAR score reduction was 87.7% (SD 3.7%). Overall record keeping scores were written records 100%, study models 99.5%, Orthopantomogram radiograph 99.2%, photographs 86.3%, medical history 75% and consent 40.8%. Conclusions: Occlusal outcomes achieved by specialist practitioners in Scotland were of a high standard. They maintained a good standard of clinical record collection in most areas examined.